Inheritance of Fields of Study - Adam Altmejd (CESifo GmbH, 2024)
University graduates are two to five times as likely to hold a degree in the field that their parents graduated from. To estimate how much of this association is caused by the education choices of parents, I exploit admission thresholds to university programs in a regression discontinuity design. I study individuals who applied to Swedish universities between 1977 and 1992 and evaluate how their enrollment in different fields of study increases the probability that their children later study the same topic. I find strong causal influence. At the aggregate level, children become 73% more likely to graduate from a field that their parent has quasi-randomly enrolled in. The effect is always positive, but varies in size across fields. Engineering, medicine, social science, and business exhibit the largest effects. For these fields, parental enrollment increases child graduation rates with between 6.0 and 9.5 percentage points. I find little evidence for comparative advantage being the key driver of field inheritance. Parental field enrollment does not increase subject-specific skills in primary school, nor do labor market returns differ by access to parents with the same degree. Rather, parents seem to function as role models, making their own field choice salient. This is indicated by the fact that children are more likely to follow parents with the same gender, and that parental enrollment in gender incongruent fields is more impactful.
Keywords: I24; J62; 330; intergenerational transmission; fields of study